Quality of life in men living with advanced and localised prostate cancer in the UK: a population-based study. Issue 3 (March 2019) - Downing, Amy; Wright, Penny; Hounsome, Luke; Selby, Peter; Wilding, Sarah; Watson, Eila; Wagland, Richard; Kind, Paul; Donnelly, David W; Butcher, Hugh; Catto, James W F; Cross, William; et al.
Summary: Background: Little is known about the health-related quality of life (HRQOL) of men living with advanced prostate cancer. We report population-wide functional outcomes and HRQOL in men with all stages of prostate cancer and identify implications for health-care delivery. Methods: For this population-based study, men in the UK living 18–42 months after diagnosis of prostate cancer were identified through cancer registration data. A postal survey was administered, which contained validated measures to assess functional outcomes (urinary incontinence, urinary irritation and obstruction, bowel, sexual, and vitality and hormonal function), measured with the Expanded Prostate Cancer Index Composite short form (EPIC-26), plus questions about use of interventions for sexual dysfunction) and generic HRQOL (assessed with the 5-level EuroQol five dimensions questionnaire [EQ-5D-5L] measuring mobility, self-care, usual activities, pain or discomfort, and anxiety or depression, plus a rating of self-assessed health). Log-linear and binary logistic regression models were used to compare functional outcomes and HRQOL across diagnostic stages and self-reported treatment groups. Each model included adjustment for age, socioeconomic deprivation, and number of other long-term conditions. Findings: 35 823 (60·8%) of 58 930 men responded to the survey. Disease stage was known for 30 733 (85·8%) of 35 823 men; 19 599 (63·8%) had stage I or II, 7209 (23·4%) stage III, and 3925 (12·8%) stage IV disease. Mean adjusted EPIC-26 domain scores were high, indicating good function, except for sexual function, for which scores were much lower. Compared with men who did not receive androgen deprivation therapy, more men who received the therapy reported moderate to big problems with hot flushes (30·7% [95% CI 29·8–31·6] vs 5·4% [5·0–5·8]), low energy (29·4% [95% CI 28·6–30·3] vs 14·7% [14·2–15·3]), and weight gain (22·5%, 21·7–23·3) vs 6·9% [6·5–7·3]). Poor sexual function was common (81·0%; 95% CI 80·6–81·5), regardless of stage, and more than half of men (n=18 782 [55·8%]) were not offered any intervention to help with this condition. Overall, self-assessed health was similar in men with stage I–III disease, and although slightly reduced in those with stage IV cancer, 23·5% of men with metastatic disease reported no problems on any EQ-5D dimension. Interpretation: Men diagnosed with advanced disease do not report substantially different HRQOL outcomes to those diagnosed with localised disease, although considerable problems with hormonal function and fatigue are reported in men treated with androgen deprivation therapy. Sexual dysfunction is common and most men are not offered helpful intervention or support. Service improvements around sexual rehabilitation and measures to reduce the effects of androgen deprivation therapy are required. Funding: The Movember Foundation, in partnership with Prostate Cancer UK.